The Text and Contexts of Ignatius Loyola's "Autobiography" - McManamon, John M. (Book collections on Project MUSE., 2013)
This refreshing re-evaluation of the so-called autobiography of Ignatius Loyola (c. 1491G1556) situates IgnatiusGs Acts against the backgrounds of the spiritual geography of LukeGs New Testament writings and the culture of Renaissance humanism. Ignatius LoyolaGs So-Called Autobiography builds upon recent scholarly consensus, examines the language of the text that Ignatius Loyola dictated as his legacy to fellow Jesuits late in life, and discusses relevant elements of the social, historical, and religious contexts in which the text came to birth. Recent monographs by Marjorie OGRourke Boyle and.